MESO-ADC: The ADC design using MESO device. (October 2021) - Zeng, Junwei; Yi, Pinyun; Chen, Boya; Huang, Chenglong; Qi, Xuelei; Qiu, Shan; Fang, Liang
Abstract: In this paper, we propose a new 3-bit ADC based on magnetoelectric spin–orbit (MESO) device. By adjusting the thickness of the magnetoelectric part of MESOs, the ADC possesses multiple switching thresholds for converting input voltages into magnetization state. By means of the iterative HSPICE analysis and Monte Carlo analysis, we quantitatively calculated the power consumption and evaluated the reliability of the ADC device. The results show that the proposed ADC could sample at an 8.3 GHz rate with 0.014 pJ conversion energy. In comparison with the NAND-SPIN based magnetic ADC (MADC), the sampling rate and power of the proposed ADC could be improved by 66% and economize up to 45.3% respectively.